Isolation of Trypanosoma brucei gambiense from cured and relapsed sleeping sickness patients and adaptation to laboratory mice. - Patient Pati Pyana; Ipos Ngay Lukusa; Dieudonné Mumba Ngoyi; Nick Van Reet; Marcel Kaiser; Stomy Karhemere Bin Shamamba; Philippe Büscher (Public Library of Science (PLoS), 2011)
BACKGROUND: Sleeping sickness due to Trypanosoma brucei (T.b.) gambiense is still a major public health problem in some central African countries. Historically, relapse rates around 5% have been observed for treatment with melarsoprol, widely used to treat second stage patients. Later, relapse rates of up to 50% have been recorded in some isolated foci in Angola, Sudan, Uganda and Democratic Republic of the Congo (DRC). Previous investigations are not conclusive on whether decreased sensitivity to melarsoprol is responsible for these high relapse rates. Therefore we aimed to establish a parasite collection isolated from cured as well as from relapsed patients for downstream comparative drug sensitivity profiling. A major constraint for this type of investigation is that T.b. gambiense is particularly difficult to isolate and adapt to classical laboratory rodents. METHODOLOGY/PRINCIPAL FINDINGS: From 360 patients treated in Dipumba hospital, Mbuji-Mayi, D.R. Congo, blood and cerebrospinal fluid (CSF) was collected before treatment. From patients relapsing during the 24 months follow-up, the same specimens were collected. Specimens with confirmed parasite presence were frozen in liquid nitrogen in a mixture of Triladyl, egg yolk and phosphate buffered glucose solution. Isolation was achieved by inoculation of the cryopreserved specimens in Grammomys surdaster, Mastomys natalensis and SCID mice. Thus, 85 strains were isolated from blood and CSF of 55 patients. Isolation success was highest in Grammomys surdaster. Forty strains were adapted to mice. From 12 patients, matched strains were isolated before treatment and after relapse. All strains belong to T.b. gambiense type I. CONCLUSIONS AND SIGNIFICANCE: We established a unique collection of T.b. gambiense from cured and relapsed patients, isolated in the same disease focus and within a limited period. This collection is available for genotypic and phenotypic characterisation to investigate the mechanism behind abnormally high treatment failure rates in Mbuji-Mayi, D.R. Congo.